Research on Relationships Between Self-Esteem and Social Activeness of Young People: Gender Differentiation Exemplified by the Kazakhstan-Uzbekistan Sample - Adlet Kariyev; Bekzod Baydjanov; Dmitriy Umnov; Meruyert Imankulova (Insight: the psychological dimensions of society, 2024)
The aim is to conduct theoretical-empirical research into peculiarities of the inclusion of self-esteem in the organization of social activeness of young people. Methods. The research participants were young students from Kazakhstan and Uzbekistan, aged from 18 to 26 years (n = 133). Valid and reliable psycho-diagnostic tools were applied: the self-esteem questionnaire (SQ) (Weinhold & Hilferty, 1983); methods for diagnosing social-psychological attitudes of an individual in the sphere of motivation and needs (SPAI) (Potemkina, 2001); the questionnaire “Diagnostics of motivators of an individual’s social-psychological activeness” (DMISPA) (Fetiskin et al., 2002). Results. It was found that the majority of respondents have a medium level of self-esteem which is a normotypical level of its adequacy. The only direct correlation between power orientation and the ability to make contacts (R = .176; p = .043) was established. The only inverse correlation of the general need for achievement with the art of self-acceptance (R = -.252; p = .003) suggests that young people lose in achieving success with an increase in attention to their personality. Comparison of the parameters of social activeness between the samples of males (Group 1) and females (Group 2) revealed the only superiority of Group 2 in the parameter “work orientation” (U = 1603.500; p = .012). Discussion and conclusions. It was substantiated that young people are considerably affected by the opinions of significant others regarding their personality. It was emphasized that a correlation between the general need for achievement with the art of self-acceptance demonstrates the self-actualization tendencies of young people aimed at impacting global social processes. There is a caveat that it may also hide a pragmatic component with hedonistic behavioral patterns. It was explained that the females’ sample is more process-oriented and focused on everyday responsibilities, which determined a significant difference in the parameter “work orientation”. It was summarized that the obtained results possess scientific value and can be of interest to anyone who works with young people. It was substantiated that the level of self-esteem has an impact on the parameters and orientation of social activeness.